1997
DOI: 10.1001/archinte.1997.00440290099011
|View full text |Cite
|
Sign up to set email alerts
|

Chaparral-Associated Hepatotoxicity

Abstract: These data indicate that the use of chaparral may be associated with acute to chronic irreversible liver damage with fulminant hepatic failure, and they underscore the potential for certain dietary supplement ingredients to cause toxic effects on the liver. Health professionals should be encouraged to inquire routinely about the use of dietary supplements and other products, to be alert to potential adverse effects that may be associated with these products, and, finally, to report any serious adverse events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In México it is reported that an infusion of the leaves dissolves gallbladder and kidney stones when the tea is consumed throughout the day ("Agua de uso"; Martínez, 1969;Diaz, 1976;Lara and Márquez, 1996). It is used in the treatment of diseases of the liver, and as a liver tonic (Sheikh et al, 1997;Brent, 1999). Creosote bush has also been employed for kidney pain and cystitis (Martínez, 1969) dysuria (Martínez, 1969;Lara and Márquez, 1996), as a diuretic (Mabry et al, 1979b;Tyler and Foster, 1999), to treat infections of the urinary tract and venereal diseases (Timmermann, 1977;Mabry et al, 1979b;Brent, 1999).…”
Section: Reported Medicinal Usesmentioning
confidence: 99%
See 3 more Smart Citations
“…In México it is reported that an infusion of the leaves dissolves gallbladder and kidney stones when the tea is consumed throughout the day ("Agua de uso"; Martínez, 1969;Diaz, 1976;Lara and Márquez, 1996). It is used in the treatment of diseases of the liver, and as a liver tonic (Sheikh et al, 1997;Brent, 1999). Creosote bush has also been employed for kidney pain and cystitis (Martínez, 1969) dysuria (Martínez, 1969;Lara and Márquez, 1996), as a diuretic (Mabry et al, 1979b;Tyler and Foster, 1999), to treat infections of the urinary tract and venereal diseases (Timmermann, 1977;Mabry et al, 1979b;Brent, 1999).…”
Section: Reported Medicinal Usesmentioning
confidence: 99%
“…It has also been used as salves against burns (Sheikh et al, 1997;Brent, 1999), bruises and hemorrhoids, for cicatrization (Argueta, 1994), chicken pox (Timmermann, 1977;Sheikh et al, 1997), snakebite pain, chronic cutaneous disorders (Nellesen, 1997;Sheikh et al, 1997;Brent, 1999) and allergic problems (Brinker, 1993).…”
Section: Reported Medicinal Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…They can cause the sinusoidal obstruction syndrome (veno-occlusive disease of the liver), 184 with clinical features that can occur. Plants that have been reported to cause acute liver damage include Breynia officinalis, 164 Callilepis laureola (ox-eye daisy), 165 Camellia sinensis (green tea), 166 Chelidonium majus (celandine), 167 Cimicifuga racemosa (black cohosh; Figure 76.21), 168,169 Larrea tridentata (chaparral), 170 Piper methysticum (kava; Figure 76.20; see below under Psychotropic drugs), Polygonum multiflorum, 171 Symphytum officinale (comfrey; see below under Sinusoidal obstruction syndrome) 172,173 and Teu crium spp. 174,175 Of these, black cohosh, chaparral, comfrey, and kava are the most common culprits.…”
Section: Impaired Platelet Aggregationmentioning
confidence: 99%